Prevention of hair graying by factors that promote the growth and differentiation of melanocytes. Issue 8 (August 2014) - Endou, Mariko; Aoki, Hitomi; Kobayashi, Tatsushi; Kunisada, Takahiro
Abstract Epidermal melanocyte precursors migrate into developing hair follicles to form the melanocyte stem cell system required to supply pigmented melanocytes necessary for hair pigmentation in repetitive hair cycles. Hair graying is caused by irreversible defects in the self‐renewal and/or development of follicular melanocyte stem cells in the hair follicles. To investigate the mechanism(s) of hair graying during the normal aging process, we established a hair graying model in mice by repeatedly plucking or shaving trunk hairs. We repeatedly plucked or shaved trunk hairs to induce and accelerate the hair graying and counted the gray hairs. By using this functional model of hair graying in mice, we assessed the effects of genes known to affect melanocyte development, such as Kitl, hepatocyte growth factor (HGF) and endotheline 3 (ET3). After increasing the total numbers of cumulative hair cycles by plucking or shaving, we observed a significant increase in the gray hair of C57BL/6 mice. Kitl expression in the skin was the most effective for preventing hair graying and a significant effect was also confirmed for HGF and ET3 expression. The repeated hair plucking or shaving led to hair graying without any genetic lesion. Kitl is a more effective factor for prevention of hair graying than HGF or ET3. Our simple model of hair graying may provide a basic tool for screening the molecules or reagents preventing the progression of hair graying.